KUALITAS PELAYANAN PUBLIK (STUDI PADA PELAYANAN ADMINISTRASI MAHASISWA DI POLITEKNIK NEGERI SRIWIJAYA (POLSRI) TAHUN 2012 - SILVANA OKTANISA (Program Studi Magister Manajemen FE Unsri, 2013)
This thesis entitled the Quality of Public Services (Study on Students Administrative Services at State Polytechnic of Sriwijaya in 2011). Formulation of the problem of this research is how the quality of student administrative services at State Polytechnic of Sriwijaya on three types of services provided, namely: service new admissions, re-registration service student and student academic administrative services. Research method used in this research is descriptive research with quantitative approach. Theory used is the model servqual with five dimensions of service quality (tangible, reliability, responsiveness, assurance, and empathy). Evaluations of the quality of service is determined by two factors: perceptions and expectations of students. Results of data analysis showed that student perceptions of student administrative at three kinds of services at middle category (2.75 to 3.61), whereas for perception score is lowest on the dimensions of responsiveness and the highest scores is the tangible dimension. Hopes of students at all three services are in very high category (4.51 to 4.80), which means that students have high expectations on the dimensions of tangible and empathy. Difference in value perceptions and expectations of students on the quality of student administrative services servqual calculations obtained negative results for all three services. It means that the quality of student administrative services at State Polytechnic of Sriwijaya yet either, because the perceived value is lower than the expected value. Focus attention directed repair services are the dimensions of responsiveness and empathy. This is supported hypothesis testing results for all three services, where the value perceptions and expectations are not the same values ​​and significant, so the quality of student administrative services said was not good.